Volume 3: Turbo Expo 2004 2004
DOI: 10.1115/gt2004-53244
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of the Flow and Thermal Development of a Row of Cooling Jets Impinging on a Rotating Concave Surface

Abstract: The paper reports an experimental study of impingement cooling in a rotating passage of semi-cylindrical cross-section. Cooling fluid is injected from a row of five jet holes along the centerline of the flat surface of the passage and strikes the concave surface. The cooling passage rotates orthogonally about an axis parallel to that of the jets. Tests have been carried out, using water, both within the passage and as the jet fluid, at a fixed Reynolds number of 15,000, for clockwise and anti-clockwise rotatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…Evidently, the central jet (Jet 3) has virtually disappeared at Ro ¼ 20.18 despite it being as strong as the others in stationary conditions. Analogous results are found for Jet 4 in clockwise rotation [33].…”
Section: Impingement Coolingsupporting
confidence: 81%
See 3 more Smart Citations
“…Evidently, the central jet (Jet 3) has virtually disappeared at Ro ¼ 20.18 despite it being as strong as the others in stationary conditions. Analogous results are found for Jet 4 in clockwise rotation [33].…”
Section: Impingement Coolingsupporting
confidence: 81%
“…Moreover, the jet principally affected differs depending upon the sense of rotation: for clockwise rotation it is the central jet that is 'extinguished', while for anti-clockwise rotation, the jet next to the top is obliterated. Flow visualization and laser-Doppler velocimetry (Iacovides et al [33]) confirmed the more rapid spread of the jets and the consequent loss of these jets' identity. This is clearly brought out in Fig.…”
Section: Impingement Coolingmentioning
confidence: 97%
See 2 more Smart Citations
“…Iacovides et al [11] researched the impinging jet under the rotation condition with Ro = 0.18. They reported that all secondary peaks and some of the primary peaks in array jets disappear due to strong rotation effect.…”
Section: Introductionmentioning
confidence: 99%